2022
DOI: 10.1002/er.7821
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer enhancement of Fe 3 O 4 ‐water nanofluid by the thermo‐magnetic convection and thermophorestic effect

Abstract: The promotion of the heat transfer by ferro-nanofluid under a magnetic field has caught more extensive attention in the field of nuclear industry and energy engineering. Firstly, a modified model based on the Buongiorno model was proposed to investigate the heat transfer considering the Kelvin force in the presence of an inhomogeneous magnetic field to elevate the heat transfer performance of nanofluid using thermomagnetic convection. Secondly, the influence of Kelvin force, thermophoresis, and Brownian motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…φ hnp (22) The following Equation ( 23) was utilized to theoretically calculate the value of the specific heat of mono nano-PCM, which is formulated according to the principle of mixture theory [44]: (23) Specific heat of hybrid nano-PCM can be estimated from Equation 24:…”
Section: Numerical Model 31 Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…φ hnp (22) The following Equation ( 23) was utilized to theoretically calculate the value of the specific heat of mono nano-PCM, which is formulated according to the principle of mixture theory [44]: (23) Specific heat of hybrid nano-PCM can be estimated from Equation 24:…”
Section: Numerical Model 31 Governing Equationsmentioning
confidence: 99%
“…They are extensively utilized in many applications, such as photocatalysis, polymer reinforcing, and heat transfer enhancement. Many studies have focused on using nanoparticles to enhance the thermal characteristics of fluids [22]. Hamali and Almusawa [23] applied the Galerkin technique to investigate water freezing with the assistance of extended surfaces and nanoparticles using a two-dimensional model.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [32] found that a streamlined channel structure can effectively reduce the pressure drop in liquid cooling systems, ensuring uniform battery temperature and improving system cooling capacity. Additionally, external forces such as magnetic and electric fields can enhance heat transfer performance by inducing chaotic convection [33][34][35]. Du et al [33] indicated that chaotic convection due to the Kelvin force, as well as the thermophoretic effect, can enhance heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, external forces such as magnetic and electric fields can enhance heat transfer performance by inducing chaotic convection [33][34][35]. Du et al [33] indicated that chaotic convection due to the Kelvin force, as well as the thermophoretic effect, can enhance heat transfer. Wang et al [34] illustrated that the main mechanism for heat transfer in MCHS is chaotic convection induced by the motion of electrophoresis and thermophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…Akhter et al [4] numerically simulated the convective heat transfer of Fe 3 O 4water nanofluids in a fan-shaped annulus cavity, and conducted the analysis on the effects of Rayleigh number, cavity structure and volume fraction of nanofluid on the heat transfer. Du et al [5] investigated the heat transfer enhancement of a MCHS in the presence of an external magnetic field, based on the Buongiorno model when the applied magnetic field and thermophorestic effect are in consideration. Wang et al [6] indicated that electrophoresis can significantly influence the heat transfer of nanofluid when external electric field is applied.…”
Section: Introductionmentioning
confidence: 99%